Strong electrostatic adsorption approach to the synthesis of sub-three nanometer intermetallic platinum–cobalt oxygen reduction catalysts. (January 2021) - Ma, Yanling; Kuhn, Andrew N.; Gao, Wenpei; Al-Zoubi, Talha; Du, Hui; Pan, Xiaoqing; Yang, Hong
Abstract: Low-platinum group metal (low-PGM) intermetallics are among the best materials as active and stable electrocatalysts for the oxygen reduction reaction (ORR) in polymer electrolyte membrane fuel cells (PEMFCs). The lack of control over the particle size and size distribution limits the use of thermal annealing method in the synthesis of carbon-supported low-PGM intermetallics because of the surface atomic diffusion at elevated temperatures. Herewith, we report the synthesis of sub-3 nm intermetallic PtCo ORR catalysts using a strong electrostatic adsorption (SEA) approach. The strong adhesion of metal ion precursors ensured to anchor the PtCo nanoparticles on the carbon support, thus suppressing the atomic migration and sintering during their conversions to intermetallic phases. The mass activity of the intermetallic PtCo catalyst was 0.67 A/mgPt (at 0.9 V vs. RHE) which was more than double that of its alloyed counterpart. Most noticeably, the mass activity of this catalyst dropped by merely 3% of its initial value after the accelerated durability test of 10, 000 cycles, in a strong acid condition. This study provides a useful strategy for preparing ultrafine low-PGM intermetallic nanocrystals for ORR and paves the way to use the SEA approach for making intermetallic ORR electrocatalysts using various metals and support materials. Graphical Abstract: ga1 Highlights: A sub-3 nm intermetallic L10 -PtCo ORR catalyst was synthesized using a strong electrostatic adsorption (SEA) approach. The acidity-dependent synthesis allows the control towards the size and dispersion of A1-PtCo nanoparticles on carbon. Strong adhesion between PtCo nanoparticles and N-doped mesoporous carbon greatly suppresses the sintering at high temperatures. The intermetallic L10 -PtCo/C electrocatalysts exhibit greatly improved activity and stability for ORR in acid conditions.